Penerapan Standarisasi Homestay di Kawasan Wisata Lembah Harau - Amarta, Cut Niken; Ferdian, Feri (Prasetiya Mulya Publishing, 2024)
This research was motivated by the fact that some guests thought they did not meet the criteria when staying at homestays in the Harau Valley tourist attraction area. This study aims to determine how the application of homestay standardization based on ASEAN homestay standards in the Harau Valley tourist attraction area. This type of research is descriptive research with quantitative approach methods. The population in this study was homestay owners totaling 112 homestays. This study used a non-probability sampling technique. The data collection technique is a questionnaire or questionnaire arranged with the guttman scale method. Furthermore, data analysis was carried out with the help of SPSS. Based on the results of the study that the application of homestay standardization in the Harau Valley tourist attraction area obtained through observation, an average score of yes was 89.15% and not 10.85% with the category interpreted almost entirely.